ORGANIZATIONAL CULTURE, LEADERSHIP STYLE, WORK MOTIVATION, AND COMPENSATION ON PERFORMANCE OF FINANCE EMPLOYEES - Yois Nelsari Malau; Ira Mayang Sari br Surbakti; Asniat Tranita Hulu; Widia Permata Sari Zendrato (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
This study aims to analyze and determine the influence of culture, organization, work motivation, leadership style, and compensation on the performance of employees in the finance department in the Medan City Government. This study uses a method with a quantitative approach, namely by using primary data derived from questionnaires through Likert scale measurements. In this study, the population in question is the whole of the State Civil Apparatus in the finance department of the Medan City Government with a total population of 231 people. The sampling in this study used a purposive sampling technique which resulted in 68 people as respondents. The data analysis method in this study is multiple linear regression whose calculations are assisted by the IM SPSS version 26 software. The results of this study indicate that: (1) there is a significant influence on organizational culture, work motivation, leadership style, and compensation for the performance of employees in the department. viewed as a stimulant, (2) there is a good influence of organizational culture, work motivation, leadership style, and the provision of compensation to the performance of employees in the finance department which is seen partially.